Visitor satisfaction analysis as a tool for park managers: a review and case study - Tonge, J.; Moore, S.; Taplin, Ross (Australian and New Zealand Association for Leisure Studies (ANZALS), 2011)
Visitor satisfaction has been an important area for leisure research since the 1960s and more recently for park management. A number of approaches have been adapted from consumer research including importance-performance analyses, gap analyses, threshold performance targets and overall satisfaction. This paper reviews these approaches with respect to park management. It then draws on focus group research with protected area agency staff to obtain their viewson the usefulness androbustness of the analyses associated with these approaches. Yanchep National Park (Western Australia) was used as a case study, with the results from a recent visitor survey providing the data for satisfaction analyses. To provide a more accurate summary of the range in results, confidence intervals accompanied the results to illustrate the variation in responses. The analyses emphasize theimportance for park managers of accessible, usable data on visitor satisfaction .